Causes of the Earth's Expansion (Global Journal of Science Frontier Research, 2022)
The article answers the question about the cause of the expansion of the Earth. The direct cause of the expansion of the Earth is the increase of basalt magma in the mantle of the globe and oceanic plates. The final answer is short, but it still requires the basic processes and laws of nature to be taken into account. Such a basic issue is explaining the issue of the existence of a heat source in the middle of the Earth and the processes of ionization and recombination of matter. The author argues with the view of the generally accepted theory of lithospheric plate tectonics that there is basically no heat source and the existing endogenous heat of the Earth is relict heat. It is also under dispute that the cause of geological activity is the drift of lithospheric plates.
Keywords: geothermal energy; earth expansion; basalt magma; thermonuclear georeactor; plasma; recombinetion